EFFECT ON BUSINESS MARKETING IMPROVED SALES (Survey On Bricks Industrial District of Ukui, Kab. Pelalawan) - Desy Alpisa; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study departs from the problems of the high level of competition inthe industry viewed from the brick sales attainment targets are not realized in thebrick industry for three years terakhir.adanya unrest in considering industrialentrepreneurs brick brick brick is a privately owned business that looks to thebrick entrepreneurs to support their families .. The purpose of this study was todetermine the marketing efforts on brick industry to increased sales and marketingefforts to effect an increase in sales (survey bricks industry in the district UkuiPelalawan. This study analyzed the data by using quantitative descriptive analysisand to answer the hypotheses that have been proposed statistical analysisperformed using simple linear regression. Results of the study concluded that theoverall marketing effort is considered to be good and increase in sales ririskiky awhole is considered very good. Based on the analysis of data through statisticalanalysis, it can be seen b ahwa independent variables (Business Marketing) has amoderate effect on the variable d ependen (Increased Sales). Variable independe(Business Marketing) provide a positive and significant effect on the variable dependen (Increased Sales), so that when the independent variables improved itwill cause an increase in the dependent variable.Keyword : Marketing efforts, Increasing Sales, Industry